2014
DOI: 10.1155/2014/178498
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization and Effect of Immobilized Thermostableβ-Glucosidase in Alginate Gel Beads on Sugarcane Juice

Abstract: A thermostable β-glucosidase was effectively immobilized on alginate by the method of gel entrapment. After optimization of immobilized conditions, recovered enzyme activity was 60%. Optimum pH, temperature, kinetic parameters, thermal and pH stability, reusability, and storage stability were investigated. The K m and V max for immobilized β-glucosidase were estimated to be 5.0 mM and 0.64 U/ml, respectively. When comparing, free and immobilized enzyme, change was observed in optimum pH and temperature from 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 39 publications
2
27
1
5
Order By: Relevance
“…This higher optimal reaction temperature indicated that the applied immobilization technique gave a greater stability to tannase (Hota et al, 2007). Hydrophobic and other secondary interactions of the immobilized enzyme might impair conformational flexibility needing higher temperatures for the enzyme molecule to recognize and attain a proper conformation in order to keep its reactivity (Keerti et al, 2014). These results are also in agreement with previous reports concerning with an increase in temperature after immobilization of tannase (Abdel-Naby et al, 1999;Hota et al, 2007).…”
Section: Temperature Optima and Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…This higher optimal reaction temperature indicated that the applied immobilization technique gave a greater stability to tannase (Hota et al, 2007). Hydrophobic and other secondary interactions of the immobilized enzyme might impair conformational flexibility needing higher temperatures for the enzyme molecule to recognize and attain a proper conformation in order to keep its reactivity (Keerti et al, 2014). These results are also in agreement with previous reports concerning with an increase in temperature after immobilization of tannase (Abdel-Naby et al, 1999;Hota et al, 2007).…”
Section: Temperature Optima and Stabilitysupporting
confidence: 92%
“…The increased substrate-enzyme affinity as indicated by decrease in K m may also slow down the product release thereby decreasing V max. Beside this decrease in V max might be attributed to limited accessibility of substrate molecules to the active sites of the enzyme and the interaction of the enzymes with the functional groups on the surface of beads or large areas of contact between enzyme and support (Keerti et al, 2014). K m values of tannase have found to be varied according to the conditions of production, with 0.6, 0.64 and 0.68 mM recorded for tannase produced by A. niger in solid state, submerged fermentation, and liquid surface fermentation, respectively (Rana and Bhat 2005).…”
Section: Kinetic Characterisation Of Tannasementioning
confidence: 99%
“…(2) Exoglucanases: exoglucanase cleaves long cellulose chains at the extremities and hydrolyses b-1,4-glucosidic bonds to release soluble cellobiose. (3) b-Glucosidases: b-glucosidases hydrolyse cellobiose and soluble cellulose oligosaccharides to produce glucose (Singh et al 2016;Keerti et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Immobilisation of β-glucosidase enzyme is an important tool for enhancement in its activity as immobilised enzyme facilitates efficient recovery and reuse of costly enzymes besides providing increased stability over wider ranges of temperature, pH and organic solvent [50]. Immobilisation of enzyme has been tried on various inorganic compounds and organic polymers like chelated magnetic metal ion nanoparticles [51], magnetic chitosan [52], alginate [53], polyacrylamide gel [54], agarose [55] and silica [56]. Immobilisation of the enzyme has been tried by both physical adsorption and covalent modification method, the main drawback being enzyme leakage and reduced activity, respectively.…”
Section: Enhancement In β-Glucosidase Activity By Enzyme Immobilisationmentioning
confidence: 99%
“…It has been also observed that immobilised enzymes differ in their physiochemical properties and increased thermo stability and different pH optima have been observed as compared to free enzyme [57]. In most of the cases, an increase in K m and decrease in V max value have been reported on enzyme immobilisation but the advantage of being used multiple times with enhanced stability at extreme range of temperature and pH makes the process economically feasible [53,60]. The use of nanoparticles for enzyme immobilisation has been found to improve biochemical properties of the entrapped enzyme [56].…”
Section: Enhancement In β-Glucosidase Activity By Enzyme Immobilisationmentioning
confidence: 99%